#TITLE_ALTERNATIVE# - RIO ADRIANSYAH (NIM 10104044), AHMAD
In this book, we study the notion of critical sets in graph labeling. Firstly, critical sets introduced by Nelder (1977), Curan, and van Rees (1978) for latin square. Then, ETB (2005) apply that concept to graph labeling. We search the numbers of critical sets from an edge magic total labeling on double star. We construct an algorithm, and presented it with some computational result. Some pictures are given to facilitate understanding. As a result, we reveal the numbers of critical sets and its pattern on double star with edge magic total labeling Kotzig Rosa and edge magic total labeling Even Odd.